PERLINDUNGAN HUKUM TERHADAP PENGGUNA JASA ANGKUTAN UDARA DALAM PERSPEKTIF PERATURAN PERUNDANG-UNDANGAN TENTANG PENERBANGAN - Muhammad Taufik Hidayat (Al-Adl : Jurnal Hukum, 2017)
The legal protection granted to the users of air transport services in Indonesia is the main thing that should be the main purpose of the rulesof law on air transport businesses, its among others is the responsibility of the airline and the settlement of compensation to passengers delay on flight schedules. Based on the results of the discussions about the problem of delays in flight schedule, the position of  service users is powerless. It is often the airline refuge on the stipulations of Article 28 of the Air Transport Ordinance in the terms of responsibility for delays in flight schedules, as such terms are standard klausula contained in airline tickets. Completion of compensation to the passengers delay on the flight schedule is still obstacle because of weak awareness of service users in their rights and there is no strict sanctions for airlines that do not carry out an obligation to award the compensate for service users delays in flight schedules.Keywords: Legal Protection, Transport, Flight